Intelligent Computing Systems First International Symposium, ISICS 2016, Mérida, México, March 16-18, 2016, Proceedings - Martin-Gonzalez, Anabel; Uc-Cetina, Victor (Communications in Computer and Information Science, 2016)
This book contains the reviewed, accepted contributions of the First International Symposium on Intelligent Computing Systems (ISICS) that was held in Merida (Mexico) from 16-18 March 2016. We received 25 submissions from 13 countries. Each submission had been evaluated by at least three members of the Program Committee and external reviewers. Based on these reviews, 12 papers were selected for long oral presentation. In addition to the contributed papers, four keynote speaker presentations were included in the conference program.